Petrological and geochemical characteristics of the Low- and High-Hf Nam Meng dioritoid, northwest Vietnam: Implication for the mantle partial melting, mixing, and magmatic differentiation - Tran, Tuan-Anh; Pham-Ngoc, Can; Nguyen, Hoang; Vu Hoang, Ly; Ngo Thi, Huong; Tran Quoc, Cong; Pham Thi Phuong, Lien; Tran Trong, Hoa; Vuong Bui Thi, Sinh; Pham Thanh, Thuy (Vietnam Journal of Earth Sciences, 2024)
This paper investigated the petrological, elemental, and isotope geochemical characteristics of the Nam Meng dioritoid to clarify the magma source and process. The Nam Meng massif comprises large amounts of dioritoids (gabbro-diorite and quartz diorite) and lesser amounts of granitoids (granodiorite and granite). The Nam Meng gabbro-diorite is a porphyritic texture with fine-grained plagioclase, amphibole, K-feldspar, and phenocryst biotite. The Nam Meng quartz diorite comprises coarse-grained plagioclase, amphibole, biotite, quartz, and K-feldspar. The Nam Meng gabbro-diorite contains higher plagioclase and lower biotite and quartz than the Nam Meng quartz diorite. The variation in petrography and mineralogy with the negative correlation between SiO2 contents with Al2O3, MgO, Al2O3 + MgO, T-Fe2O3, and CaO contents suggest a magmatic differentiation process. All the Nam Meng dioritoids have low ACNK (mostly less than 1.0), total alkaline (Na2O + K2O ≤ 6 wt.%) with Na2O/K2O ≥ 1, and negative anomalies of Ta, Nb, and Ti. Combined with the U-Pb zircon age of 290 Ma (Hieu et al. (2017), the Nam Meng dioritoid is thought to be an I-type granitic rock formed in the subduction stage of the Indosinian amalgamation event. The low La/Yb ratios (1.14-3.21) suggest that the mantle wedge that was melted to form the Nam Meng magma had a spinel peridotite composition. The εNd (290 Ma) of the Nam Meng dioritoid is close to bulk earth silicate at 290 Ma (-4.43 to 2.34). The 87Sr/86Sr (290 Ma) of the Nam Meng dioritoid varies in a wide range from low to intermediate (0.6987 to 0.7088), and the calculated Nd model age of the Nam Meng dioritoid is 1,258 ± 47 Ma. The Sr and Nd isotope data suggest that the Nam Meng spinel peridotite was a result of mixing between an ancient ocean crust, EM1, and EM2 that occurred in a paleo-subduction zone at Meso-Neoproterozoic Rodinia supercycle. The Hf contents of the low-Hf and high-Hf Nam Meng dioritoid series are 0.38-1.02 and 2.60-8.08, respectively. The LILE/Hf and HSFE/Hf ratios in the low-Hf Nam Meng dioritoids are high and have a strongly negative correlation with Hf. On the other hand, those ratios in the high-Hf Nam Meng dioritoids are low and have a weakly negative correlation with Hf. The Hf contents positively correlate with the degree of partial melting of the mantle wedge in the subduction zone. Therefore, the low Hf, high LILE/Hf, and HSFE/Hf ratios of the Nam Meng dioritoids could be derived from a low degree of partial melting of the mantle wedge. In contrast, the high Hf, low LILE/Hf, and HSFE/Hf ratios of the Nam Meng dioritoids could be produced by a high degree of partial melting of the mantle wedge.